A Nationwide Survey of Oral Health Related Quality of Life of Children With Orofacial Cleft in New Zealand. (August 2021) - Fowler, Peter V.; Ayrey, S. Louise; Stone, Peter R.; Thompson, John M. D.
Objectives: To describe (1) oral health related quality of life (OHRQoL) for children with orofacial cleft (OFC) in New Zealand and (2) assess any differences in OHRQoL by sex, ethnicity, and cleft phenotype using the 16 item (and 8 item subset) of the Child Perception Questionnaire (CPQ) and Parent version (P-CPQ). Design and Setting: Prospective cross-sectional nationwide study. Methods and Materials: Children with OFC and their parents completed the 16-item CPQ or the Parent CPQ, respectively, when attending cleft clinic appointments between January 2015 and December 2017. Results: Overall, 174 children (mean age 10.4 ± 1.2 years) and their parents (n = 181) completed the CPQ or P-CPQ. In multivariable analysis, neither the CPQ nor P-CPQ 16-item or 8-item subset showed significant differences in OHRQoL total score with cleft phenotype. Children with cleft lip and palate (CLP) had higher (worse) well-being scores than those with cleft palate alone (CP) on the P-CPQ. Pacific Island children had consistently higher scores across both CPQ and P-CPQ, total and subscales. Conclusions: Significant differences in OHRQoL among children with OFC were found for the well-being domain for children with CLP as reported by P-CPQ, but the symptom domain and total score showed no differences. Poorer scores were reported for children of Pacific Island descent using both questionnaires. The study findings indicate that children with OFC in New Zealand are a group who experience worse OHRQoL when referenced to normative non-OFC data. Further investigations are required to establish greater insight into specific factors influencing OHRQoL.